1997
DOI: 10.1021/jp970937v
|View full text |Cite
|
Sign up to set email alerts
|

Geometries and Energies of Nitrobenzene Studied by CAS-SCF Calculations

Abstract: Optimized geometries and energies in the ground (S0) and excited states of nitrobenzene were calculated using the CAS-SCF method. The optimized geometries in the S1, S2, T1, T2, and T3 states are very different from that in the S0 state. Most significantly, the nitro group is largely bent out of the phenyl plane in the excited states. The potential curves along the nitro rotation coordinate around the C−N bond and the out-of-plane bending mode of the nitro group in the S0, S1, T1, and T2 states were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
74
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 34 publications
9
74
0
Order By: Relevance
“…Similar conclusions have been drawn for nitrobenzene and p-nitroaniline. 14,16 On the other hand, the gas-phase equilibrium geometry of NPe*(S 1 ) is predicted to be planar ( Figure 9B). Moreover, the potential along the torsional coordinate is not as shallow as that for the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions have been drawn for nitrobenzene and p-nitroaniline. 14,16 On the other hand, the gas-phase equilibrium geometry of NPe*(S 1 ) is predicted to be planar ( Figure 9B). Moreover, the potential along the torsional coordinate is not as shallow as that for the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…They also obtained the substitution r s -structure and calculated the height of the barrier hindering internal rotation to be 2.9 ± 0.3 kcal/mol. The calculations of optimized geometries and energies in the ground (S 0 ) and excited electronic states of NB by the multiconfiguration method in complete active space (CAS SCF) demonstrated that the energy gap between S 0 and the nearest excited state (T 1 ) may reach *50-60 kcal/mol [5]. The energy of the triplet T 1 state in solution was deduced to be 58 kcal/mol [6].…”
Section: Literature Data On Spectroscopy Studiesmentioning
confidence: 99%
“…The low-lying n,π* levels are due to the presence of nonbonding lone-pair orbitals on the oxygen atoms of the nitro group. It has been suggested that the fast ISC of nitroarenes is caused by strong coupling between the excited singlet and triplet states, both of which show large distortions of the nitro group relative to the geometry of the ground state (Takezaki et al 1998;Takezaki et al 1997b). Nitrobenzene also shows no phosphorescence, due to the short lifetime of the lowest excited triplet state (Takezaki et al 1997a).…”
Section: Nitroarenesmentioning
confidence: 99%